An Assessing Speaking Ability: Insights from English Conversation Club among Fifth-Semester Midwifery Students - Harahap, Yulinda Oktaviana; Harahap, Yulina Oktaviani (Universitas Majalengka, 2024)
This study explores the speaking abilities of 5th-semester students involved in the English Conversation Club (ECC) within a Midwifery Diploma Study Program. The research focuses on understanding the challenges faced by students in speaking English and evaluating the ECC's contribution to enhancing their speaking skills. The investigation utilized a mixed-methods approach involving qualitative and quantitative data collection.The study found that while most students performed well, as indicated by their scores falling under the